TINJAUAN ASPEK DEMOGRAFI DENGAN PERILAKU VAKSIN HPV PADA WANITA USIA SUBUR (WUS) - Nilam Noorma; Hendra Yulita; Mukhlisiana Ahmad; Lia Indria Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Cancer is one of the leading causes of death worldwide and remains a major challenge in public health. According to data from the Indonesian Pathology Center, cervical cancer is one of the most common types of cancer affecting the Indonesian population and ranks highest among cancers that affect women. The purpose of this study was to determine the relationship between demographic aspects and HPV vaccination behavior among women of reproductive age (WRA). The research design used in this study was a cross-sectional approach. The study was conducted in the Pulo Gadung District in April 2025. The sample consisted of 86 respondents, selected using a purposive sampling technique. The research instrument used was a questionnaire, and data analysis was carried out using univariate and bivariate methods. The results showed a relationship between knowledge (p-value: 0.000) and family support (p-value: 0.002) with HPV vaccination behavior among women of reproductive age. It is recommended that respondents increase their knowledge and awareness regarding the importance of cervical cancer prevention by actively seeking information from reliable sources, such as healthcare professionals, community health centers, hospitals, and official health education media. Women of reproductive age are also expected to pay greater attention to their reproductive health by engaging in early preventive measures.Keywords: HPV, Cervical Cancer, Women of Childbearing Age.